2004
DOI: 10.1074/jbc.m408450200
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Bacterial Organic Hydroperoxide Detoxification System in Preventing Catalase Inactivation

Abstract: In the gastric pathogen Helicobacter pylori, catalase (KatA) and alkyl hydroperoxide reductase (AhpC) are two highly abundant enzymes that are crucial for oxidative stress resistance and survival of the bacterium in the host. Here we report a connection unidentified previously between the two stress resistance enzymes. We observed that the catalase in ahpC mutant cells in comparison with the parent strain is inactivated partially (approximately 50%). The decrease of catalase activity is well correlated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 40 publications
1
43
0
1
Order By: Relevance
“…Among these, the most abundant one is AhpC. Several functional studies of H. pylori AhpC have shown that the AhpCdeleted mutants have increased sensitivity to oxygen (15), overexpress neutrophil-activating protein (18), and accelerate inactivation of catalase (25). As a member of 2-Cys peroxiredoxins (17,21,31), AhpC has been shown to be Trx-dependent (17,27,32,33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, the most abundant one is AhpC. Several functional studies of H. pylori AhpC have shown that the AhpCdeleted mutants have increased sensitivity to oxygen (15), overexpress neutrophil-activating protein (18), and accelerate inactivation of catalase (25). As a member of 2-Cys peroxiredoxins (17,21,31), AhpC has been shown to be Trx-dependent (17,27,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…To combat the reactive oxygen species released from the host immune system and survive in the gastric mucosa, pathogenic H. pylori is equipped with a number of detoxifying proteins (25,31). Among these, the most abundant one is AhpC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes were inactivated by inserting antibiotic resistance cassettes (kanamycin and chloramphenicol for Msr and catalase, respectively) as described previously (16,19). H. pylori strains were grown in Brucella agar (BD Biosciences) plates containing 10% defibrinated sheep blood (Quad Five, Ryegate, MT).…”
Section: Methodsmentioning
confidence: 99%
“…In H. pylori, catalase is one of the most abundant proteins (constitutes ϳ4 -5% of the total proteins, described herein), and it has some unique properties. Its unusual characteristics include a high pI (Ͼ9.0) (18) and high resistance to H 2 O 2 (19). Although an H. pylori catalase mutant (katA) strain is viable in vitro under nonoxidative stress conditions, catalase activity has been shown to be associated with the resistance of the bacterium to professional phagocytes and macrophages (20,21).…”
mentioning
confidence: 99%